Resources and race: assisted reproduction in Ecuador - Roberts, Elizabeth F.S. (Reprod Biomed Soc Online, 2016)
This article considers the early period of development of IVF in Ecuador, focusing on factors that shaped the decade after the nation's first successful IVF birth (1992–2002). It describes how a poorly resourced public healthcare sector compelled Ecuadorians towards private-sector medicine, which included assisted reproduction treatment, and how IVF clinics drew patients through the pervasive racial inequalities that characterise post-colonial Ecuadorian society. More generally, the development of assisted reproduction treatment in Ecuador exemplifies themes in 20th century healthcare provisioning and inequality in Latin America, making it essential to understand this larger picture when considering Ecuador’s IVF industry both within the region and also internationally.